Acetabular labrum blood flow in developmental dysplasia of the hip: an intraoperative in vivo study using laser Doppler flowmetry. Issue 1 (December 2016) - Minokawa, So; Naito, Masatoshi; Kinoshita, Koichi; Yamamoto, Takuaki
Abstract Background The vascular supply to the acetabular labrum is important in the treatment of labral lesions. However, in vivo blood flow measurements in the acetabular labrum have not been described in the literature. The purpose of this study was to examine this blood flow in vivo using laser Doppler flowmetry (LDF) in patients with acetabular dysplasia. Methods Periacetabular osteotomy combined with arthroscopy was performed in 47 consecutive patients (three males, 44 females; mean age at surgery, 35.6 years; range, 15–60 years). In all patients, blood flow in the acetabular labrum was measured with LDF during arthroscopy. The acetabular labral lesions were categorized according to the modified Beck classification: detachment and full-thickness labral tears were assigned to the T group and normal labrum to the N group. Blood flow rates in the acetabular labrum were compared between the T and N groups. The associations between labral blood flow and the lateral center-edge angle (CEa) and patient age were also evaluated. Results The T and N groups comprised 31 and 16 patients, respectively. The mean blood flow rate was 1.94 ± 0.41 ml/min/100 g in the T group and 1.94 ± 0.34 ml/min/100 g in the N group, with no significant difference between the groups (P  = 0.884). No association was noted between blood flow and either the CEa or patient age (β  = −0.018, P  = 0.077 andβ  = −0.001, P  = 0.770, respectively). Conclusions On LDF, blood flow in the acetabular labrum was present in all patients, regardless of the severity of acetabular labral tears, CEa, or age.